An overview of the protection of children rights under Islamic law - Mohd, Azizah; Ibrahim, Badruddin; Alkali, Alhaji Umar (American Scientific Publishers, 2017)
Islamic law outlines a comprehensive of children’s rights that deserve protection. These are related toin many sources of Islamic law (the Shari’ah) which include the Quran, the Sunnah, Secondary Sources e.g., ‘urf and juristic discourse. Such rights include the right to lineage (nasab), right to care and custody, the right to maintenance, the right to the good name, the right to love and affection and so forth. Children’s rights are also protected based on the general aim of the Shari’ah: (maqasid al-Shari’ah) i.e., securing benefit to all mankind and protect them from any harm. As protection of children’s rights are vital but violated by many nowadays, this paper seeks to study on the protection of children’s rights under Islamic law. It aims at providing a critical overview of overall principles for the protection of children’s rights in Islam based on the Qur’an and Sunnah of the Prophet (PBUH). It is hoped that this research will provide a basic understanding on children rights in Islam that require attention and safeguards from all.